Bus management system - Hasdilazira, Abd Latif (2005)
Bus Management System is a system that developed to make the management of bus driver and bus trip at Transnasional Express Sdn Bhd Kuantan Branch become easier.At this time, this company only has online ticketing system and still do not has computerized management system for their company operation.Therefore,all the data and information that related with driver and bus trip is documented and kept in file base system.Manual system in record keeping make an important data or information has a potential to lost or damage.Besides,driver scheduling is assigned by operation officer manually and the operation officer must prepare the schedule everyday before the driver start their trip. Therefore,computerized driver scheduling is suggested to make the management of driver schedule become easier.RAD model is used as a process model and Microsoft Visual Basic 6.0 and Microsoft Access is used as a tool for Bus Management System development.Besides, the prototype for bus management system successfully developed to make the management work become more effective.